Seismic Risk Assessment of Buildings in Dubai, United Arab Emirates - Al Shamsi, Gaith Abdulrahman (2013)
A Master of Science thesis in Civil Engineering by Gaith Abdulrahman Al Shamsi entitled, "Seismic Risk Assessment of Buildings in Dubai, United Arab Emirates," submitted in June 2013. Thesis advisor is Dr. Mohammad AlHamaydeh. Available are both soft and hard copies of the thesis.